2022
DOI: 10.1108/ejim-05-2022-0230
|View full text |Cite
|
Sign up to set email alerts
|

Green supply chain management and innovation persistence–Based on environmental turbulence perspective

Abstract: PurposeIn recent years, environmental issues and resource depletion have posed significant challenges to firms and society. To address these environmental challenges, firms seek to build strategic alliances of green supply chain management (GSCM) with their supply chain partner. As the largest developing country in the Asia–Pacific region, China needs to take more responsibility for environmental protection, which requires more Chinese firms to participate in GSCM. Therefore, focusing on the issue of GSCM and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…In the approach above, a comparable estimate of the inner wide range works well for SEM. (Yu & Xiao, 2022) contemplates using SEM by utilizing this form of the complete low-squares technique (PLS) for endeavors analogous to ours in management science research. We followed the advice provided by someone who offered additional information on selecting between PLS-SEM and Covariance-Based (CB) SEM as the kind of SEM to use.…”
Section: Discussionmentioning
confidence: 99%
“…In the approach above, a comparable estimate of the inner wide range works well for SEM. (Yu & Xiao, 2022) contemplates using SEM by utilizing this form of the complete low-squares technique (PLS) for endeavors analogous to ours in management science research. We followed the advice provided by someone who offered additional information on selecting between PLS-SEM and Covariance-Based (CB) SEM as the kind of SEM to use.…”
Section: Discussionmentioning
confidence: 99%
“…According to Jaworski and Kohli [53], we categorize the characteristics of the environment faced by firms into market turbulence, competitive intensity, and technological turbulence. It has been shown that environmental turbulence can provide substantial opportunities for enterprises to improve their sustainable competitiveness [54]. The effect of digital technology adoption on digital transformation performance is likely to be greater when the market environment faced by an organization is more volatile, competitive, or technologically up-to-date.…”
Section: Moderating Effects Of Environmental Characteristics Of Enter...mentioning
confidence: 99%